Determinants of credit risk: Comparative study of banks in China, UK and US - wu, ying jun (2013)
As the on-going financial crisis and its tremendous influence sweeping around the world, governments and the participants of financial market have raised their attentions on the potential risk management of large complex financial institutions. Banks as the specific and crucial organizations in financial market have attracted much more attentions. With the bankruptcy of Lehman Brothers Holdings Inc. in the US, the Northern Rock bank event occurred in Britain and many other bank failures came up from 2008 to 2010, there are many researchers and policymakers starting to focus on the indicators that could probably explain these failures and attempt to developing some early warning systems that could give some signals where a crisis is likely to occur. According to the insolvency theory, the majority of bank’s assets are in the form of loans, credit risk could drives large amount of non-performance loans which might cause the value of assets fall consequently, it demonstrates a bank would fails when the value of bank assets fall and finally less than its liabilities. Therefore, we can infer that the bank’s credit risk can be treated as a major risk that drives banks’ failure. This paper is attempt to address the general significant determinants that drive bank’s credit risks based on panel data regression and relevant statistical techniques and making a comparative analysis of bank’s credit risk and its influencing factors among three particular countries- China, UK and US. Finally, the paper will illustrate empirical analysis to find out the different credit risk exposures of three countries’ banking sectors under the context of financial crisis. This paper will provide valuable conclusion and recommendations for further research.